Tissue Engineering to Repair Diaphragmatic Defect in a Rat Model. (27th August 2017) - Liao, G. P.; Choi, Y.; Vojnits, K.; Xue, H.; Aroom, K.; Meng, F.; Pan, H. Y.; Hetz, R. A.; Corkins, C. J.; Hughes, T. G.; Triolo, F.; Johnson, A.; et al.
Abstract : Tissue engineering is an emerging strategy for repairing damaged tissues or organs. The current study explored using decellularized rat diaphragm scaffolds combined with human amniotic fluid-derived multipotent stromal cells (hAFMSC) to provide a scaffold, stem cell construct that would allow structural barrier function during tissue ingrowth/regeneration. We created an innovative cell infusion system that allowed hAFMSC to embed into scaffolds and then implanted the composite tissues into rats with surgically created left-sided diaphragmatic defects. Control rats received decellularized diaphragm scaffolds alone. We found that the composite tissues that combined hAFMSCs demonstrated improved physiological function as well as the muscular-tendon structure, compared with the native contralateral hemidiaphragm of the same rat. Our results indicate that the decellularized diaphragm scaffolds are a potential support material for diaphragmatic hernia repair and the composite grafts with hAFMSC are able to accelerate the functional recovery of diaphragmatic hernia.